Local faith-based tourism and volunteers within related entities: A Maltese perspective - Cassar, Oliver (The international journal of religious tourism and pilgrimage, 2020)
In 2017 a research study was carried out by the Cultural Commission of the Pinto Philharmonic Society (Socjetà Filarmonika Pinto Banda San Sebastjan) of Qormi, Malta. This study aimed to evaluate the perceptions of volunteers that are active in different non-governmental organizations within different Christian parishes around Malta and Gozo. Within the research confraternities in diffe rent parish, local band clubs and chivalric orders had been identified as particular entities having good potential to enhance the niche market formation for faith-based tourism. Although volunteers recognise the positive inputs from tourism, the research also discusses local traditions. Further discussed is the apparent lack of communication between different stakeholders of faith-based tourism, and the authorities, which may result in misconceptions and misunderstandings. It could also be concluded that NGO's also may not have the necessary empowerment to implement and develop new ideas within this market. The lack of stakeholder participation in the planning and policy-making process is also highlighted.